Thoracic Spinal Anaesthesia for Modified Radical Mastectomy in a Patient with Pulmonary Atelectasis & Pleural Effusion: Case Report - Irawan, Dino; Herman, Awanda (Jurnal Medika Malahayati, 2024)
The incidence of breast cancer is the highest malignancy in Indonesia, and this case increases with age, affecting more than 65% of patients over 65 years old.  In geriatric patients, the possibility of coexisting major medical problems is high, which makes anesthetic management challenging, Regional anesthesia is a preferable option for breast cancer surgery for geriatrics with coexisting major medical problems than general anesthesia.Spinal anesthesia has more advantages compared with general anesthesia. These include smaller respiratory and cardiac complications, better intraoperative and postoperative pain control, early recovery of gastrointestinal function, lower postoperative nausea and vomiting, early ambulation and discharge from hospital, a reduced need for blood transfusions, and reduced costs. A significant advantage of spinal anesthesia in this case is the avoidance of airway instrumentation and its possible complications. Studies have demonstrated that up to 15 to 20% of the lung at its base collapses during uneventful anesthesia before any surgical intervention. Pulmonary atelectasis and pleural effusion increase the risk of ventilator dependence after anesthesia.